Transdisiplinaritas Dalam Pendidikan Islam - Putra, Purniadi (Analisis: Jurnal Studi Keislaman, 2017)
Human as mysterious creatures cannot if only be approached by a scientific discipline, they must be understood in an interdisciplinary manner. In writing this journal explaining the possibility of Islamic education has a transdisciplinary meaning to eliminate the separation between general science and the science of religion and all the knowledge developed is related to one another. The method used is the method of discourse analysis and content. The way in which a number of literatures is discussed and analyzed is based on the direction and purpose of the transdisciplinary concept. The results of the discussion in the context of the transdisciplinary Islamic education curriculum must be developed to be holistic in nature that can cover a variety of problems inherent in humans and their development. The ability to achieve it in transdisciplinary Islamic education is the ability to see the world as a value system, each of which has different tasks and functions but still interconnected. This interconnection connection system must be placed in the framework of faith and noble character.